Impact of salt and exogenous AM inoculation on indigenous microbial community structure in the rhizosphere of dioecious plant, Populus cathayana - Na Wu (Nature Portfolio, 2021)
Abstract The sex-specific physical and biochemical responses in dioecious plants to abiotic stresses could result in gender imbalance, and how to ease the current situation by microorganisms is still unclear. Using native soil where poplars were grown, growth parameters, soil physicochemical properties in the rhizosphere soil of different sexes of Populus cathayana exposed to salt stress and exogenous arbuscular mycorrhizal (AM) inoculation were tested. Besides, the sex-specific microbial community structures in the rhizosphere soil of different sexes of Populus cathayana were compared under salt stress. To identify the sex-specific microbial community characteristics related to salinity and AM symbiosis, a combined qPCR and DGGE method was used to monitor microbial community diversity. Seedlings suffered severe pressure by salt stress, reflected in limited growth, biomass, and nutrient element accumulation, especially on females. Exogenous AM inoculation treatment alleviated these negative effects, especially under salt treatment of 75 mM. Compared with salt effect, exogenous AM inoculation treatment showed a greater effect on soil physical–chemical properties of both sexes. Based on DGGE results, salt stress negatively affected fungal richness but positively affected fungal Simpson diversity index, while exogenous AM inoculation treatment showed the opposite effect. Structural equation modeling (SEM) was performed to show the causal relationships between salt and exogenous AM inoculation treatments with biomass accumulation and microbial community: salt and exogenous AM inoculation treatment showed complicated effects on elementary concentrations, soil properties, which resulted in different relationship with biomass accumulation and microbial community. Salt stress had a negative effect on soil properties and microbial community structure in the rhizosphere soil of P. cathayana, whereas exogenous AM inoculation showed positive impacts on most of the soil physical–chemical properties and microbial community status.